Ketorolac Tromethamine Loaded Nano-Spray Dried Nanoparticles: Preparation, Characterization, Cell Viability, COL1A1 Gene Simulation and Determination of Anti-inflammatory Activity by In vivo HET-CAM Assay - æ#150;ztürk, A.A.; æ#135;evikelli, T.; Tilki, E.K.; Güven, U.M.; Kıyan, H.T. (Current Drug Delivery, 2023)
Background: Ketorolac tromethamine (KT) is a non-steroidal anti-inflammatory drug from the heteroaryl acetic acid derivatives family. The most widely used new nanotechnological approaches for topical drug delivery are polymeric nanoparticles (NPs). Objective: Successful results have been obtained with low doses in many treatments, such as cancer, antimicrobial, pain, made with nanoparticle formulations of drug active ingredients. Methods: NPs were prepared using Nano Spray-Dryer. The cytotoxicity of the optimum formulation in BJ (ATCC® CRL-2522™) human fibroblast cells was determined by the WST- 1 method and the gene activity was elucidated by mRNA isolation and real-time polymerase chain reaction (RT-PCR). The in vivo HET- CAM assay was performed for anti-inflammatory activity. Results: NPs presented PDI values lower than 0.5, and therefore particle size distribution was decided to be monodisperse. Positive zeta potential values of NPs highlighted the presence of the cationic ammonium group of Eudragit® RS 100. The release rates observed from KT-NP coded formulations after 24 hours were 78.4% ± 2.9, demonstrating extended release from all formulations, relative to pure KT. The lowest concentration of KT-NP increased fibroblast cell proliferation higher than the highest concentration of KT. The 5-fold increased effect of KT-NP formulation on collagen gene expression compared to KT is also related to the enhanced anti-inflammatory effect in line with the in vivo HET-CAM assay results. Conclusion: With the obtained cell viability, gene expression, and HET-CAM results, it has the hope of a successful nano-topical formulation, especially in both wound healing and anti-inflammatory treatment.
Keywords: COL1A1